Computational Linguistics and Intelligent Text Processing : 16th International Conference, CICLing 2015, Cairo, Egypt, April 14-20, 2015, Proceedings, Part II - Gelbukh, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The two volumes LNCS 9041 and 9042 constitute the proceedings of the 16th International Conference on Computational Linguistics and Intelligent Text Processing, CICLing 2015, held in Cairo, Egypt, in April 2015. The total of 95 full papers presented was carefully reviewed and selected from 329 submissions. They were organized in topical sections on grammar formalisms and lexical resources; morphology and chunking; syntax and parsing; anaphora resolution and word sense disambiguation; semantics and dialogue; machine translation and multilingualism; sentiment analysis and emotion detection; opinion mining and social network analysis; natural language generation and text summarization; information retrieval, question answering, and information extraction; text classification; speech processing; and applications.
Sentiment Analysis and Emotion Detection -- The CLSA Model: A Novel Framework for Concept-Level Sentiment Analysis -- Building Large Arabic Multi-domain Resources for Sentiment Analysis -- Learning Ranked Sentiment Lexicons -- Modelling Public Sentiment in Twitter: Using Linguistic Patterns to Enhance Supervised Learning -- Trending Sentiment-Topic Detection on Twitter -- EmoTwitter - A Fine-Grained Visualization System for Identifying Enduring Sentiments in Tweets -- Feature Selection for Twitter Sentiment Analysis: An Experimental Study -- An Iterative Emotion Classification Approach for Microblogs -- Aspect-Based Sentiment Analysis Using Tree Kernel Based Relation Extraction -- Text Integrity Assessment: Sentiment Profile vs Rhetoric Structure -- Sentiment Classification with Graph Sparsity Regularization -- Detecting Emotion Stimuli in Emotion-Bearing Sentences -- Sentiment-Bearing New Words Mining: Exploiting Emoticons and Latent Polarities -- Identifying Temporal Information and Tracking Sentiment in Cancer Patients Interviews -- Using Stylometric Features for Sentiment Classification -- Opinion Mining and Social Network Analysis -- Automated Linguistic Personalization of Targeted Marketing Messages Mining User-Generated Text on Social Media -- Inferring Aspect-Specific Opinion Structure in Product Reviews Using Co-training -- Summarizing Customer Reviews through Aspects and Contexts -- An Approach for Intention Mining of Complex Comparative Opinion Why Type Questions Asked on Product Review Sites -- TRUPI: Twitter Recommendation Based on Users Personal Interests -- Detection of Opinion Spam with Character n-grams -- Content-Based Recommender System Enriched with Wordnet Synsets -- Active Learning Based Weak Supervision for Textual Survey Response Classification -- Detecting and Disambiguating Locations Mentioned in Twitter Messages -- Natural Language Generation and Text Summarization Satisfying Poetry Properties Using Constraint Handling Rules -- A Multi-strategy Approach for Lexicalizing Linked Open Data -- A Dialogue System for Telugu, a Resource-Poor Language -- Anti-Summaries: Enhancing Graph-Based Techniques for Summary Extraction with Sentiment Polarity -- A Two-Level Keyphrase Extraction Approach -- Information Retrieval, Question Answering, and Information Extraction Conceptual Search for Arabic Web Content -- Experiments with Query Expansion for Entity Finding -- Mixed Language Arabic-English Information Retrieval -- Improving Cross Language Information Retrieval Using Corpus Based Query Suggestion Approach -- Search Personalization via Aggregation of Multidimensional Evidence About User Interests -- Question Analysis for a Closed Domain Question Answering System -- Information Extraction with Active Learning: A Case Study in Legal Text -- Text Classification -- Term Network Approach for Transductive Classification -- Calculation of Textual Similarity Using Semantic Relatedness Functions -- Confidence Measure for Czech Document Classification -- An Approach to Tweets Categorization by Using Machine Learning Classifiers in Oil Business -- Speech Processing -- Long-Distance Continuous Space Language Modeling for Speech Recognition -- A Supervised Phrase Selection Strategy for Phonetically Balanced Standard Yoruba Corpus -- Semantic Role Labeling of Speech Transcripts -- Latent Topic Model Based Representations for a Robust Theme Identification of Highly Imperfect Automatic Transcriptions -- Probabilistic Approach for Detection of Vocal Pathologies in the Arabic Speech -- Applications -- Clustering Relevant Terms and Identifying Types of Statements in Clinical Records -- Medical Entities Tagging Using Distant Learning -- Identification of Original Document by Using Textual Similarities -- Kalema: Digitizing Arabic Content for Accessibility Purposes Using Crowdsourcing -- An Enhanced Technique for Offline Arabic Handwritten Words Segmentation.
Keywords: Natural language processing (Computer science).; Computational linguistics; Information storage and retrieva; Artificial intelligence; Data mining; Natural Language Processing (NLP).; Computational Linguistics; Information Storage and Retrieval; Artificial Intelligence; Natural Language Processing (NLP).; Data Mining and Knowledge Discovery